2017
DOI: 10.1007/s10461-017-1982-4
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Stigma Patterns Among Nigerian Men Who Have Sex with Men and Their Link to HIV and Sexually Transmitted Infection Prevalence

Abstract: Sexual stigma facilitates the spread of HIV and sexually transmitted infections (STIs) but little is known about stigma affecting Nigerian men who have sex with men (MSM). We assessed patterns of sexual stigma across Nigerian MSM and their relationship to HIV and STIs. Data were collected from the TRUST/RV368 Study, a prospective cohort of 1480 Nigerian MSM enrolled from March 2013 to February 2016 using respondent driven sampling. Structural equation modeling was utilized to assess the association between sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 51 publications
1
25
0
Order By: Relevance
“…Other qualitative studies have shown that sexual and gender minorities avoid testing because a diagnosis of HIV or rectal STIs could lead to unintended disclosure of anal sex practices [4,31,32]. We have previously reported substantial anticipated and enacted stigma surrounding disclosure of same sex sexual practices by participants in our cohort [7,33‐35]. Despite the goal of non‐stigmatizing care delivery in our clinics, it is possible that participants who had not previously been tested for HIV had experiences that affirmed their anticipated stigma and reduced likelihood of retention.…”
Section: Discussionmentioning
confidence: 90%
“…Other qualitative studies have shown that sexual and gender minorities avoid testing because a diagnosis of HIV or rectal STIs could lead to unintended disclosure of anal sex practices [4,31,32]. We have previously reported substantial anticipated and enacted stigma surrounding disclosure of same sex sexual practices by participants in our cohort [7,33‐35]. Despite the goal of non‐stigmatizing care delivery in our clinics, it is possible that participants who had not previously been tested for HIV had experiences that affirmed their anticipated stigma and reduced likelihood of retention.…”
Section: Discussionmentioning
confidence: 90%
“…An especially effective combination may be to use SNS and internet recruitment with HIVST in order to optimize both reach and delivery of HIV testing services. Studies of Nigerian MSM have found high utilization of online dating sites, high proportions of participants who identified as bisexual, and low prevalences of disclosure of same-sex behavior,[33,65,66] particularly among MSM exposed to sexual stigma, and thus a combined recruitment approach with HIVST could reach MSM who fear stigma at testing facilities. A study that collaborated with an MSM community-based organization (CBO) in Kenya to deliver HIVST using peer educators resulted in high levels of opt in and reached a higher percentage of undiagnosed MSM than did clinic-based testing.…”
Section: Discussionmentioning
confidence: 99%
“…Nine indicators of stigma were included as an aggregate measure of stigma. [33] The aggregate stigma measure included any lifetime experiences of seven types of enacted stigma (family made discriminatory remarks, rejection from friends, refusal from police to protect, verbal harassment, blackmail, physical violence, and rape) and two types of felt stigma (fear of seeking health care and fear of walking in public) that participants felt were due to the fact that they had sex with men. These indicators have been found to be common among MSM in the US, West Africa, and Southern Africa.…”
Section: Methodsmentioning
confidence: 99%
“…39,40 The study also identified a substantial need for diagnosis and management of other sexually transmitted infections, and new prevention interventions. [40][41][42][43][44][45][46][47] Study findings have subsequently been incorporated directly into prevention and clinical service approaches at the community centers.…”
Section: Rv516mentioning
confidence: 99%